Ask the right questions, hire the best people, fourth edition : hire the best people, fourth edition - Fry, Ronald W. (Highbridge Audio, 2018)
In this completely updated new edition, the bestselling author of 101 Great Answers to the Toughest Interview Questions and 101 Smart Questions to Ask on Your Interview takes you step-by-step through the hiring process. Whether you're replacing an employee who's leaving or creating a new position in your organization, Ron Fry shows you how to write a concise and accurate job description, identify key competencies, and how to translate them into a realistic set of search criteria. Ask the Right Questions, Hire the Best People also shows you: &#9679 How to attract the best applicants. &#9679 What to look for when you're screening resumes, in your office or online. &#9679 What questions you should ask in the interview ... and when to ask them. &#9679 How to listen more effectively to what the applicant is really telling you. &#9679 How to probe for information the applicant doesn't want to reveal. &#9679 What questions the law permits and forbids.